Pendidikan Kesehatan Tentang Pencegahan Covid-19 Terhadap Pengetahuan, Sikap dan Perilaku pada Lansia (STIKes Surya Global Yogyakarta, 2023)
Background: Healthy according to the basic health law of 2009 in chapter 1 article 1 is a condition that includes physical, spiritual, spiritual and social health, and also independent and productive personality. According to WHO, the elderly is someone who has entered the age of 60 years and over. The elderly experience various health problems, especially those related to the aging process including: hypertension, cancer, mental disorders, and other increasing man made diseases (Ministry of Health, 2013). Many people are worried about the transmission of Covid -19 disease. One of the red zones is Sleman area. The signs and symptoms are fever, with some cases having difficulty breathing, and X-rays showing extensive infiltrate pneumonia in both lungs (WHO, 2020). The purpose of this study is to determine the effect of health education on the prevention of Covid-19 on the knowledge, attitudes and behavior of the elderly in Kragan Tempel Village, Sleman.Methods: This research was a pre-experimental one group pretest and posttest. Respondents in the study were 65 respondents with a total sampling technique. The intervention provided was health education which was carried out for 1 time with duration of 15 minutes. The data were collected by using questionnaire with Wilcoxon test data analysis.Results: Based on the multivariate test, it was known that the sig value for the effect of health education on the prevention of Covid-19 on the knowledge of the elderly was 0.002 0.05 and the t value was 3.270 t table 2,000, so it can be concluded that there was significant effect of health education on preventing Covid-19 on behavior of the elderly in Kragan Tempel Village, Sleman.Conclusion: There was an effect of health education on the prevention of Covid-19on the knowledge, attitudes and behavior of the elderly in the village of Kragan Tempel Sleman.